Konstruksi Pertentangan Norma Hukum dalam Skema Pengujian Undang-Undang - Lailam, Tanto (Jurnal Konstitusi, 2014)
The study elaborated on the construction of “conflict of legal norms” in constitutional review scheme. There are eleven problems as result of this study, which include: The ideology of the state “Pancasila” as a standard review of “conflict of legal norms” act against 1945 constitution; Constitutional court has a review of act passed before and after 1945 Constitution amendment with standard of 1945 constitution; 1945 constitution is “the living constitution” for the enforcing of law and justice; Constitutional court has authority to review of act against 1945 constitution by vertical and horizontal perspective; enforceability aspect of constitutional review is a part of material review, not formal review; the meaning of “conflict of legal norms” must be comprehend elaborated in the decisions to enforcing of law and justice; Constitutional Court does not used priority of the original intent interpretation and remained unfulfilled of other model interpretation if original intent interpretation caused ineffectiveness of constitution; non constitution be permitted for the formal review, but in material review is not implement; “nemo judex idoneus in propria causa” of procedural law principle can remained unfulfilled by “ius curia novit” principle to promote of the 1945 constitution; the formal review of “conflict of legal norms” can remained unfulfilled by utility principle to priority of legal substance; the retroactive decision caused legal  uncertainly.